2001
DOI: 10.1109/20.950960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impurities on resistivity of electrodeposited high-B/sub s/ CoNiFe-based soft magnetic thin films

Abstract: Controlling the very small amount of inclusion of impurity elements by addition to the plating bath of various organic additives was found to be very effective in developing electrodeposited high-s CoNiFe soft magnetic thin films with desirably high resistivity. Included impurities were suggested to cause not only electron scattering but also decreasing grain size, both of which led to an increase of the resistivity. Chemical state of impurities was indicated to be controllable by selection of additives based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
(9 reference statements)
0
13
0
Order By: Relevance
“…In our previous work, a film with high B s value was successfully deposited by increasing the FeSO 4 concentration in the plating solution, but this resulted in a high H c value. Moreover, a high concentration of Fe ions leads to the destabilization of the solution [19] prepared, and a method for stabilizing the plating solution was established.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, a film with high B s value was successfully deposited by increasing the FeSO 4 concentration in the plating solution, but this resulted in a high H c value. Moreover, a high concentration of Fe ions leads to the destabilization of the solution [19] prepared, and a method for stabilizing the plating solution was established.…”
Section: Introductionmentioning
confidence: 99%
“…Some additives are employed to increase resistivity by incorporating S, 15,16 C, 17,18 and B. 19 Other additives are used to reduce stress and improve the appearance of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Deposits obtained from electrolytes containing additives are reported to decrease the saturation magnetization and increase the coercivity. [15][16][17][18] The reported saturation magnetization from electrolytes with additives ranged from 1.5 to 1.9 T. The lowest in-plane coercivity in electrodeposited CoNiFe alloys is obtained in additive-free electrolytes, which is associated with a nanocrystalline structure where body-centered-cubic ͑bcc͒ and face-centered-cubic ͑fcc͒ CoNiFe phases coexist with grain sizes between 10 and 20 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that an increase in the resistivity can be achieved by co-deposition with a metalloidforming element such as sulfur [20,21] or carbon [59,60]. It is suggested that the inclusion of impurities can result in an increase in resistivity [61]. [29].…”
Section: Conife Alloy Filmsmentioning
confidence: 99%